PERAN PENGAJARAN IPS, SEJARAH, DAN PKN SEBAGAI UPAYA UNTUK PEMBANGUNAN KARAKTER GENERASI BANGSA - Andik Wahyun Muqoyyidin (Fak. Tarbiyah UIN Maliki Malang, 2012)
The condition of Indonesian social life in the last decade is very crucial. Frequently the group-conflict happens, either between social or ethnic groups or between students or the young one another. Uncontrolled moral ethics and drugs in them are also in serious condition. To overcome such problems, we need an educational program of character building or revitalization of character education. Thus in place and reasonable that all providers of education institutions and students of education, busy thinking about it, how efforts to improve the character of the nation through the revitalization of character education is to be implemented in educational institutions. The revitalization of character education is implemented in integrated and holistic approach, not as a school subject. Thus, most of them who are involved within the program must be a model of a good character as stated in the national norm which is based on Pancasila culture. Besides, they work together holistically, in integrative way, and comprehensively. Purpose of this literature review is to examine the role of teaching Social Studies, History, and Civics in an effort to build the character generation using qualitative methods and take the kind of library research. The results from the literature review showed that while there is a great role of teaching Social Studies, History, and Civics to participate and build the character of the generation of reliable and virtuous character.